2018
DOI: 10.18632/oncotarget.25747
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral immune-biomarkers and mismatch repair status in leiyomyosarcoma -potential predictive markers for adjuvant treatment: a pilot study

Abstract: Leiomyosarcoma is the second most frequent soft-tissue sarcoma. Tumor lymphocytic infiltration (TIL) and programed cell death ligand-1 (PD-L1) have been associated with prognosis in different malignancies while DNA mismatch-repair deficiency (MMR-D) has been associated with response to check-point inhibitors. In this pilot study, we sought to examine TIL, PD-L1 and mismatch-repair (MMR) protein expression in 11 leiomyosarcoma and its association with outcome as potential biomarkers for adjuvant treatment.Eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Cohen et al ., have recently shown in a small cohort of 11 LMS cases that CD3+ TILs were present in both the central (11/11) and periphery (9/9) regions of the tumour. In their study, CD8+ TILs were found in a subset of cases in the central (10/11) and periphery (7/9) of the tumour 41 . Given the small number of cases assessed in both studies, further evidence in larger cohorts is required to determine if these observations are generally applicable to LMS and other STS subtypes.…”
Section: Discussionmentioning
confidence: 88%
“…Cohen et al ., have recently shown in a small cohort of 11 LMS cases that CD3+ TILs were present in both the central (11/11) and periphery (9/9) regions of the tumour. In their study, CD8+ TILs were found in a subset of cases in the central (10/11) and periphery (7/9) of the tumour 41 . Given the small number of cases assessed in both studies, further evidence in larger cohorts is required to determine if these observations are generally applicable to LMS and other STS subtypes.…”
Section: Discussionmentioning
confidence: 88%
“…However, few models have been proposed to predict the prognosis of LMS. Cohen et al observed the association between tumor infiltrating CD8 cytotoxic lymphocytes, PD-L1 staining, expression of mismatch repair-related proteins (MSH2, MLH1, MSH6 and PSM2) and survival in patients with LMS [ 54 ]. Studies from Xue et al suggested that age greater than 60 years, high tumor grade, distant metastasis, tumor size ≥ 5 cm, and lack of surgery were associated with decreased OS and cancer-specific survival [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on DDLPS and pleomorphic liposarcomas [41,64], myxofibrosarcoma [38,41], fibrosarcoma [41], desmoplastic small round cell tumor [29,66], osteosarcoma [38,58,64,67], UPS [38,64], and pleomorphic dermal sarcoma [39] report less than half the cases show PD-L1 expression on the sarcoma cells. In comparison, PD-L1 was expressed on the neoplastic cells in more than half of leiomyosarcoma [35,37,41] and giant cell tumor specimens [58].…”
Section: Pd-l1mentioning
confidence: 96%
“…A majority of studies find CD8+ T cells to be more abundant [11,[32][33][34] relative to FOXP3+ T regulatory cells [32][33][34][35][36]. When divided based on karyotype complexity, copy number-driven sarcomas (DDLPS [11], leiomyosarcoma [35,37], UPS, and myxofibrosarcoma [38]) had higher T cell infiltration than translocation-associated subtypes [11]. In rhabdomyosarcomas, the copy number-and mutationdriven embryonal subtype has more CD3+ and CD8+ T cell infiltration than its translocation-associated counterpart, alveolar rhabdomyosarcoma [36].…”
Section: T Cell Infiltration: Cd3 Cd4 Cd8 Foxp3mentioning
confidence: 99%
See 1 more Smart Citation